Cooled Radiofrequency Ablation of the Trochanteric Branch of the Nervus Femoralis to Treat Greater Trochanteric Pain Syndrome. Issue 8 (27th June 2021) - Abd-Elsayed, Alaa; Cui, Chen; Eckmann, Maxim S
Abstract: Objective: Greater trochanteric pain syndrome is a common cause of lateral hip pain. Corticosteroid injections are commonly utilized as nonsurgical interventions; however, they are not effective for all patients. This technical case report describes a method for treating greater trochanteric pain syndrome by utilizing cooled radiofrequency ablation. Methods: The trochanteric branch of the nervus femoralis is identified as providing sensory innervation to the greater trochanter and its surrounding structures. We have identified fluoroscopic targets to block the nerve and perform cooled radiofrequency ablation. We present two patient cases which demonstrated significant pain relief of greater trochanteric pain syndrome with this treatment. Conclusions: Cooled radiofrequency ablation of the trochanteric branch of the nervus femoralis is a potential treatment for greater trochanteric pain syndrome. This procedure provides a potential steroid-sparing interventional treatment based on reproducible fluoroscopic landmarks.